Effects of Mother Tongue Interference in the Learning of English Intonation - Benjamin F.C. Nwokedi (International Journal of Sustainable Applied Sciences, 2023)
The learning of English intonation by non-native speakers is a nuanced process significantly influenced by the interference of their mother tongue. This interference, often categorized under linguistic interference or language transfer, manifests in various facets of English language acquisition, including the critical aspect of intonation. Intonation, which encapsulates the variation in pitch while speaking, is integral to the effective communication and comprehension of spoken English. This study delved into the multifaceted impacts of mother tongue interference on English intonation learning, with a particular focus on how phonological and suprasegmental features of a learner's first language influence their ability to acquire and produce the correct English intonation. Through a review of existing literature and examination of practical examples, the study highlights the challenges faced by learners, especially in academic settings, and suggests potential pedagogical strategies to mitigate the negative effects of mother tongue interference. The findings underscore the necessity for a tailored approach in teaching English intonation to non-native speakers, taking into consideration the phonological characteristics of their mother tongue to foster a more conducive learning environment for mastering English intonation.